2018
DOI: 10.1212/nxi.0000000000000501
|View full text |Cite
|
Sign up to set email alerts
|

Varied antibody reactivities and clinical relevance in anti-GQ1b antibody–related diseases

Abstract: ObjectiveTo investigate the relationship between antibody reactivities against glycolipid complexes and clinical features in Miller Fisher syndrome (MFS), Bickerstaff brainstem encephalitis (BBE), and Guillain-Barré syndrome with ophthalmoplegia (GBS-OP).MethodsUsing glycoarray, antibodies against 10 glycolipid antigens (GM1, GM2, GM4, GD1a, GD1b, GQ1b, galactocerebroside, lactosylceramide, GA1, and sulfatide) and 45 glycolipid complexes consisting 2 of the glycolipids were examined in the sera of 63 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Regarding the distribution of GBS electrophysiological variants, our analysis showed that COVID-19-associated GBS manifests prevalently with AIDP and, to a lesser extent, with AMSAN and AMAN, in line with classic GBS in Western countries [ 66 , 85 ]. Conversely, the observation of positive anti-GD1b antibodies in one COVID-19-related MFS patient and negative anti-ganglioside antibodies in other five cases appear in discordance with the high prevalence (≈ 90%) of anti-GQ1b antibodies among non-COVID-19 MFS cases [ 86 ], and may suggest different immune-mediated mechanisms. However, these results could not be generalized until a wider population would be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the distribution of GBS electrophysiological variants, our analysis showed that COVID-19-associated GBS manifests prevalently with AIDP and, to a lesser extent, with AMSAN and AMAN, in line with classic GBS in Western countries [ 66 , 85 ]. Conversely, the observation of positive anti-GD1b antibodies in one COVID-19-related MFS patient and negative anti-ganglioside antibodies in other five cases appear in discordance with the high prevalence (≈ 90%) of anti-GQ1b antibodies among non-COVID-19 MFS cases [ 86 ], and may suggest different immune-mediated mechanisms. However, these results could not be generalized until a wider population would be tested.…”
Section: Discussionmentioning
confidence: 99%
“…GD1b is one of the most represented gangliosides in nerve tissues, but has been less studied than its GQ1b and GM1 counterparts [ 10 ]. Anti-GD1b antibodies have been described in the clinical spectrum of Guillain–Barré syndrome, Miller Fisher syndrome and Bickerstaff brainstem encephalitis, and are associated with more severe disease and slower recovery [ 11 , 12 ]. More recently, anti-GD1b IgG antibodies were reported in a COVID-19 patient with Miller Fisher syndrome [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Antibodies to GQ1b gangliosides are found to be highly prevalent in MFS, BBE, and in GBS with ophthalmoplegia. 35 The high abundance of GQ1b gangliosides in extraocular neuromuscular junctions, muscle spindles, dorsal root ganglia, and possibly lower brainstem structures (reticular formation and vagal nerve) can explain the typical clinical presentation of these syndromes, [36][37][38] while the presence of other antibodies (such as GM1, GM1b, GD1a, or GalNAc-GD1antibodies) further explains the possible variability in clinical spectrum and overlap with other GBS variants. 38 A summary of the associations between GBS clinical presentations and different antibodies can be found in ►Table 1.…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%